AIDS NA REDE:UMA ABORDAGEM COMUNICACIONAL - Sanches, Conceição Aparecida (2006)
This research aims to investigate whether a group of university students from São Paulo city has a dangerous sexual behavior towards HIV, what is the group s knowledge about HIV and what are its most frequent doubts about the subject. It has also a specific aim of investigating the group s use of Internet in order to solve doubts, its strategies of searching and faith on the information found. In this perspective, our job is a descriptive and exploratory research with qualitative character. A digital questionnaire was elaborated and answered on a notebook by 400 students at the gate of 4 Faculties from North, South, East and West Regions of São Paulo 100 students each. This research is done completely under the Brazilian Laws, especially as allowed by CNS 196/96 Resolution of National Health Counselor. In order to process, analyze data and verify its variants, quantitative proceedings were used. Finally, in order to contextualize our research, it was done a Health and Communication Historical panorama that articulates the methodological orientation of the bibliographical and documental research.